The boat galley cookbook : 800 everyday recipes and essential tips for cooking aboard - Shearlock, Carolyn (International Marine/McGraw-Hill, 2013)
"No matter what anyone tells you, boat cooking IS different from cooking ashore. The space is smaller, there's no grocery store 5 minutes away, you have fewer prepared foods and electric appliances, and food storage is much different. Despite cruising different oceans, we--Jan and Carolyn--both faced the same challenges: eating well while having time to enjoy all the other great aspects of cruising. We love to snorkel, swim, kayak, explore--and just sit and admire the view. We learned with the cookbooks we both had aboard, and wished for information that wasn't available--like when Jan ended up with a frozen chicken complete with head and feet and no instructions on how to cut it up. When we couldn't get foods such as sour cream, English muffins, spaghetti sauce or yogurt, we adapted recipes to make our own. Other times, we experimented with substituting ingredients--maybe the result wasn't identical, but it was still tasty. We ended up with over 150 substitutions and dozens of "make it yourself" options.As we traded recipes and knowledge with each other, we realized we were compiling information that became The Boat Galley Cookbook: 800+ recipes made from readily-obtainable ingredients with hand utensils, including numerous choices to suit every taste: not just one cake but 20, 16 ways to prepare fish, 10 regional barbeque sauces, and so on. Step-by-step directions to give even "non-cooks" the confidence they can turn out tasty meals without prepared foods. Detailed instructions on unfamiliar things like making yogurt and bread, grilling virtually every food imaginable, preparing and cooking freshly-caught fish and seafood, cutting up and boning meat, cooking in a Thermos and baking on the stove top, as well as lots of tips on how to do things more easily in a tiny, moving kitchen. All this in an easy-to-navigate format including side tabs on the Contents to help you find your way and extensive cross reference lists at the end of each chapter. Quick Reference Lists provide idea starters: suggestions of included recipes for such categories as Mexican, Asian, and Potluck. The Boat Galley Cookbook is designed to help you every step of the way. We hope it becomes a trusted reference on your boat, and a source of many enjoyable meals"--